Beyond the 'Mediterranean city': socioeconomic disparities and urban sprawl in three Southern European cities. Issue 3 (3rd July 2017) - Zambon, Ilaria; Serra, Pere; Sauri, David; Carlucci, Margherita; Salvati, Luca
ABSTRACT: Swimming pools are together an exemplificative outcome of urban sprawl and an indicator of socio-spatial polarizations in metropolitan regions. A comparative analysis of the spatial distribution of pools in three Mediterranean cities (Barcelona, Rome and Athens) provides an alternative reading of recent urbanization in southern Europe, questioning the supposed homogeneity in socioeconomic patterns and processes across the region. In the present study, the socio-spatial structure underlying dispersed urban expansion in these three cities was studied using 53 background indicators at the spatial scale of municipalities. Four indicators were proposed to study variability in the spatial distribution of pools. Relevant differences between cities were observed in the density of pools, reflecting heterogeneous patterns of dispersed urbanization and class segregation: socioeconomic polarization in Athens, settlement scattering and social mix in Rome and a more balanced socio-spatial structure in Barcelona. The spatial distribution of pools in the three cities was found associated with different socioeconomic factors, outlining the role of spatial disparities between high-income and low-income neighbourhoods, the diverging economic base and place-specific attributes. Results from Barcelona, Rome and Athens case studies provide contrasting views of the relationship between class segregation and the local socioeconomic context. The resulting patterns of sprawl reflect distinct urban models belying the supposed homogeneity of the 'Mediterranean city' archetype.